Shareholder Value Creation During R&D Innovation And Commercialization Stages - Kelm, Kathryn M.; Narayanan, V. K.; Pinches, George E. (Academy of Management Journal, 1995)
We examined the impact on the market value of firms' stock of announcements about R&D projects made in the innovation and commercialization stages of the R&D process. Technology- and market-related variables were tested as predictors of the wealth impact of R&D announcements. Our analysis indicates that the stage of the R&D process moderates the relationship between the wealth effects and technology and market variables. The former are more important than market variables in the innovation stage, and both are important during commercialization.